Responsiveness of health care services towards the elderly in Tanzania: does health insurance make a difference? A cross-sectional study - Paul Joseph Amani; Malale Tungu; Anna-Karin Hurtig; Angwara Denis Kiwara; Gasto Frumence; Miguel San Sebastián (BMC, 2020)
Abstract Background Responsiveness has become an important health system performance indicator in evaluating the ability of health care systems to meet patients' expectations. However, its measurement in sub-Saharan Africa remains scarce. This study aimed to assess the responsiveness of the health care services among the insured and non-insured elderly in Tanzania and to explore the association of health insurance (HI) with responsiveness in this population. Methods A community-based cross-sectional study was conducted in 2017 where a pre-tested household survey, administered to the elderly (60 + years) living in Igunga and Nzega districts, was applied. Participants with and without health insurance who attended outpatient and inpatient health care services in the past three and 12 months were selected. Responsiveness was measured based on the short version of the World Health Organization (WHO) multi-country responsiveness survey study, which included the dimensions of quality of basic amenities, choice, confidentiality, autonomy, communication and prompt attention. Quantile regression was used to assess the specific association of the responsiveness index with health insurance adjusted for sociodemographic factors. Results A total of 1453 and 744 elderly, of whom 50.1 and 63% had health insurance, used outpatient and inpatient health services, respectively. All domains were rated relatively highly but the uninsured elderly reported better responsiveness in all domains of outpatient and inpatient care. Waiting time was the dimension that performed worst. Possession of health insurance was negatively associated with responsiveness in outpatient (− 1; 95% CI: − 1.45, − 0.45) and inpatient (− 2; 95% CI: − 2.69, − 1.30) care. Conclusion The uninsured elderly reported better responsiveness than the insured elderly in both outpatient and inpatient care. Special attention should be paid to those dimensions, like waiting time, which ranked poorly. Further research is necessary to reveal the reasons for the lower responsiveness noted among insured elderly. A continuous monitoring of health care system responsiveness is recommended.